Advancing Public Health Using Regulatory Science to Enhance Development and Regulation of Medical Products: Food and Drug Administration Research at the Center for Biologics Evaluation and Research - Kusinitz, Marc; Braunstein, Emily; Wilson, Carolyn A. (Frontiers in Medicine, 2017)
CBER research enhances and supports regulatory decision-making and policy development. This work contributes to our regulatory mission, advances medical product development, and supports FDA’s regulatory response to public health crises. This review presents some examples of our diverse scientific work undertaken in recent years to support our regulatory and public health mission.